PERSEPSI PETERNAK PADA KEPEMIMPINAN PENDAMPING DAN HUBUNGANNYA DENGAN PRODUKTIVITAS USAHA TERNAK DI PAGUYUBAN AL-AWWALIYAH, PASIRWANGI, GARUT, JAWA BARAT - Dwi Indah Sulistiani; Ujang Maman; Junaidi J (Departement of Agribusiness Faculty of Science and Technology, 2018)
Objective of this research; 1) determine the perception of ranchers against the properties and behavior of the leadership of the companion in the Society of Al-Awwaliyah 2) analyze the relationship between productivity breeder with productivity of livestock in the Society of Al-Awwaliyah 3) identify the relationship perceptions of ranchers against the leadership companion with productivity of livestock in the Society of Al-Awwaliyah , The data used in this study are primary and secondary data. Primary data were obtained from questionnaires which stem from ranchers while secondary data sourced from literature in the form of books and articles. Data processing was performed using Chi-square analysis using SPSS software version 21. One of the factors relating to the productivity of ranchers is the perception of ranchers against the leadership of their companion. Leadership companion views of the nature and behavior of which is owned by a companion. Productivity ranchers indirectly related to the productivity of the cattle business. Characteristics breeder visits of age, years of education, experience ranchers, and businesses in addition to ranchers. The results of data analysis showed that there is a significant relationship between business other than ranchers with ranchers productivity. The relationship between the perception of the nature of the companion breeder with productivity ranchers produce Pearson Chi-Square value is 9.751 and Asymp. Sig. (2-sided) of 0.002. This is due to interest ranchers against leadership qualities possessed by a companion who produce prolific ranchers. Ranchers consider that a companion of his leadership qualities are ideal as a companion.